2012
DOI: 10.3109/08820538.2011.626356
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Curve after Phacoemulsification in Patients with Pseudoexfoliation Syndrome and Cataract

Abstract: Early cataract extraction with IOL can smooth out intraocular pressure fluctuations in patients with pseudoexfoliation and associated cataract with open or narrow angles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…We had an average of 3.5 mm Hg reduction in mean diurnal IOP variation at 6 month post cataract surgery which is comparable to a report by Rao A. 21 In this study, diurnal IOP variation, as well as minimum, peak, and mean IOP were significantly less two months after cataract surgery in PEX irrespective of preoperative anterior chamber depth. Therefore, we can postulate that crystalline lens in PEX syndrome may be one of the sources of IOP rise and fluctuation with some mechanisms other than changes in angle width.…”
Section: Discussionsupporting
confidence: 89%
“…We had an average of 3.5 mm Hg reduction in mean diurnal IOP variation at 6 month post cataract surgery which is comparable to a report by Rao A. 21 In this study, diurnal IOP variation, as well as minimum, peak, and mean IOP were significantly less two months after cataract surgery in PEX irrespective of preoperative anterior chamber depth. Therefore, we can postulate that crystalline lens in PEX syndrome may be one of the sources of IOP rise and fluctuation with some mechanisms other than changes in angle width.…”
Section: Discussionsupporting
confidence: 89%
“… [4] , [7] From a clinical perspective, early lens removal in the earlier stages may theoretically prevent further progression of the disease. [22] Some of the eyes with classical form showed a wave like pattern of deposits anterior to the curled up classical exfoliation membrane with globular deposits atop a stalk, indicating that these deposits were washed off in a wave form resultant to iris movement (or rather pupillary movement under physiologic conditions) over the lens. The globular deposits at the “bank” would therefore represent deposits which were washed to the “shore” (periphery to centre) by iris movement.…”
Section: Discussionmentioning
confidence: 99%
“…[78910111213] Recent studies also demonstrated that phacoemulsification decreased diurnal IOP fluctuations in patients with pseudoexfoliation syndrome with open or occludable angles and decreased nocturnal IOP fluctuation in patients with primary angle closure. [2223] However, such IOP reductions may not always occur after phacoemulsification, and cataract surgery may even raise IOP postoperatively. [824] In the present study, we found that IOP was reduced (from 13.8 ± 1.9 mmHg to 12.6 ± 2.1 mmHg) after phacoemulsification when measured by GAT in the sitting position ( P = 0.007).…”
Section: Discussionmentioning
confidence: 99%